2008
DOI: 10.1007/s11920-008-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative identity disorder and schizophrenia: Differential diagnosis and theoretical issues

Abstract: Schizophrenia and dissociative identity disorder (DID) are typically thought of as unrelated syndromes--a genetically based psychotic disorder versus a trauma-based dissociative disorder--and are categorized as such by the DSM-IV. However, substantial data exist to document the elevated occurrence of psychotic symptoms in DID; awareness of these features is necessary to prevent diagnostic confusion. Recent research has also pointed out that schizophrenia and DID overlap not only in psychotic symptoms but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 30 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…In addition, there is a body of evidence showing overlap between mechanisms underlying dissociative symptoms and schizophrenia as proposed by Bleuler. Following Janet's definition of dissociation, Bleuler described that the process of splitting in schizophrenia is the same as splitting of psychic connections in hysteria and can lead to manifestations of alter personalities and typical amnesia (Janet, 1890;Bleuler and Brill, 1924;van der Hart and Friedman, 1989;Bob, 2003;Foote and Park, 2008;Moskowitz, 2008). In this context, a high prevalence of trauma history found both in schizophrenia (Read et al, 2005;van Os and Kapur, 2009) and dissociative identity disorder has been documented in recent studies (Spiegel, 1997;Kihlstrom, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a body of evidence showing overlap between mechanisms underlying dissociative symptoms and schizophrenia as proposed by Bleuler. Following Janet's definition of dissociation, Bleuler described that the process of splitting in schizophrenia is the same as splitting of psychic connections in hysteria and can lead to manifestations of alter personalities and typical amnesia (Janet, 1890;Bleuler and Brill, 1924;van der Hart and Friedman, 1989;Bob, 2003;Foote and Park, 2008;Moskowitz, 2008). In this context, a high prevalence of trauma history found both in schizophrenia (Read et al, 2005;van Os and Kapur, 2009) and dissociative identity disorder has been documented in recent studies (Spiegel, 1997;Kihlstrom, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[7] However Schizophrenia and dissociative disorders share several common symptoms such as aberrant perceptual experiences and disruptions in reality testing and studies have shown considerable confusion in the diagnosis of Schizophrenia and Dissociative Disorders based on the presence of Schneiderian first rank symptoms that are present in both the disorders. They include auditory hallucinations, delusional thinking and thought insertion/withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true at the very acute stage of schizophrenic illness with florid positive symptoms and confusion. After this period, we were able to show good psychometric properties of the DES and to infer that it may not be a problem of the psychological instrument per se, but a failure of current descriptive and categorical diagnostic nomenclature and limitation of medical philosophy of bio-genetic model of schizophrenic illness (Foote & Park, 2008).…”
Section: Validitymentioning
confidence: 91%